Association between Stigma, ARV Therapy and Complications ofPsychiatric Disorders iIn HIV / AIDS Patients - Wicaksono, Yamaji Adi; Fitrikasari, Alifiati; Sofro, Muchlis Achsan Udji; Peni, Hari (Jurnal Penyakit Dalam Indonesia, 2018)
Introduction. Stigma and discrimination among HIV/AIDS patients cause varrious problems such as physical, psychological, and social. Therefore, its management requires comprehensive intervention. Antiretroviral therapy improves the patient’s clinical course, but may lead to neuropsychiatric complications especially anxiety disorders, depression, and psychotic disorders. This study aimed to know the associationbetween stigma,ARV therapy and complications of psychiatric disorders of HIV patients. Methods. A cross-sectional study was conducted among HIV/AIDS patients undergoing antiretroviral therapy in VCT-CST RSUP dr. Kariadi and RSUD RAA Soewondo Pati. Subjects were recruited using consecutive sampling method. Asessment of disorders and stigma was conducted using Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I) and Questionnaire scale perception of PLWHA on community HIV/AIDS stigma. Analysis was performed using SPSS program. Correlation test analyzed with chi square test. Results. Total of 102 subjects were included in this study. The majority of subjects was male (51%) and the age mean value was 35.88 (SD 8.24) years. The most common type of antiretroviral drugs bas lamividine+zidovudine) + nevirapine (52.9%). The highest stigma scale of PLHIV was 95.1% positive stigma. Characteristics of psychiatric disorders consisted of 89.2% experienced psychiatric disorders, most depression 30.4%, and 6.9% psychotic disorders. Analysis showed that there was a statistically significant association between type of ARV therapy and psychiatric disorder. There was no statistically significant association between stigma and psychiatric disorders. Conclusions. There is an association between type of ARV therapy andpsychiatric disorders, but no association found between stigma and psychiatric disorders